Harmonic distortion contribution for the transmission loss allocation in deregulated energy market: a new scheme for industry consumer - Nojeng, Syarifuddin (Korean Society of Mechanical Engineers, 2015)
The industry has rapidly growth and energy supply technology advanced are become main factor which to contribute of the harmonic losses. This problem is one aspect that may affect the capability of the transmission line and also to the efficiency of electricity. This paper proposes a new scheme to allocate the cost pertaining to transmission loss due to harmonics. The proposed method, called as Generalized Harmonic Distribution Factor, uses the principle of proportional sharing method to allocate the losses among the transmission users especially for industry consumers. The IEEE 14- and 30 bus test system is used to compare the proposed method with existing method. The results showed that the proposed method provided a scheme better in allocating the cost of transmission loss, which could encourage the users to minimize the losses.